11β-hydroxysteroid dehydrogenases: A growing multi-tasking family. (15th April 2021) - Gomez-Sanchez, Elise P.; Gomez-Sanchez, Celso E.
Abstract: This review briefly addresses the history of the discovery and elucidation of the three cloned 11β-hydroxysteroid dehydrogenase (11βHSD) enzymes in the human, 11βHSD1, 11βHSD2 and 11βHSD3, an NADP + -dependent dehydrogenase also called the 11βHSD1-like dehydrogenase (11βHSD1L), as well as evidence for yet identified 11βHSDs. Attention is devoted to more recently described aspects of this multi-functional family. The importance of 11βHSD substrates other than glucocorticoids including bile acids, 7-keto sterols, neurosteroids, and xenobiotics is discussed, along with examples of pathology when functions of these multi-tasking enzymes are disrupted. 11βHSDs modulate the intracellular concentration of glucocorticoids, thereby regulating the activation of the glucocorticoid and mineralocorticoid receptors, and 7β-27-hydroxycholesterol, an agonist of the retinoid-related orphan receptor gamma (RORγ). Key functions of this nuclear transcription factor include regulation of immune cell differentiation, cytokine production and inflammation at the cell level. 11βHSD1 expression and/or glucocorticoid reductase activity are inappropriately increased with age and in obesity and metabolic syndrome (MetS). Potential causes for disappointing results of the clinical trials of selective inhibitors of 11βHSD1 in the treatment of these disorders are discussed, as well as the potential for more targeted use of inhibitors of 11βHSD1 and 11βHSD2.